Inflammatory and anti‐inflammatory cytokines in the seminal plasma of infertile men suffering from varicocele. (6th October 2016) - Zeinali, M.; Hadian Amree, A.; Khorramdelazad, H.; Karami, H.; Abedinzadeh, M.
Summary: Varicocele is one of causes of the declined sperm quality and low sperm production, which can lead to infertility in males. There are several experimental and epidemiological findings which support the idea that inflammatory mechanisms play an essential role in varicocele pathogenesis. Besides, in this pathological state, interleukin‐37 (IL‐37) as an anti‐inflammatory cytokine is able to bind interleukin‐18‐binding protein (IL‐18BP), and subsequently binds IL‐18 receptor β, inhibiting the pro‐inflammatory activity of IL‐18. To explore the interaction between IL‐37 and IL‐18 in infertility, we measured the amount of these cytokines in the seminal fluid of infertile men affected by varicocele. The seminal plasma levels of IL‐37 and IL‐18 were measured in 75 infertile men with varicocele and 75 healthy fertile controls (age range, 30–48 years) using enzyme‐linked immunosorbent assay. The seminal levels of IL‐37 and IL‐18 were significantly increased in infertile men with varicocele when compared to fertile controls ( p < .0001). Because of the essential role(s) of cytokines in inflammatory response of cell systems, it could be possible that sperm motility is reduced following increased IL‐18, activated neutrophils and reactive oxygen species in semen of infertile patients with varicocele. Moreover, the results of this study indicated that interaction between IL‐37 and IL‐18Rβ can lead to reduced inflammatory responses. It seems that IL‐37 might be a potential biomarker and therapeutic target for male infertility.